2015
DOI: 10.7727/wimj.2014.088
|View full text |Cite
|
Sign up to set email alerts
|

Sex Hormone Binding Globulin Gene Polymorphism and Risk of Type2 Diabetes Mellitus in Egyptian Men

Abstract: ABSTRACT

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 28 publications
0
1
0
Order By: Relevance
“…It has been reported that SHBG down-regulation increased the estradiol to regulate glucose metabolism among Egyptian T2DM cases. The rs6257 allele carriers were correlated with SHBG down-regulation, while the SHBG up-regulation was observed in rs6259 allele carriers [ 134 ].…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported that SHBG down-regulation increased the estradiol to regulate glucose metabolism among Egyptian T2DM cases. The rs6257 allele carriers were correlated with SHBG down-regulation, while the SHBG up-regulation was observed in rs6259 allele carriers [ 134 ].…”
Section: Introductionmentioning
confidence: 99%